2019
DOI: 10.1111/imj.14312
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia presenting with diabetes insipidus

Abstract: A 41‐year‐old man was diagnosed with hypogonadotropic hypogonadism managed with gonadotropins after routine fertility review. Eight months later he presented with new polydipsia and polyuria, lethargy and easy bruising. A full blood count showed 28% circulating blasts. A bone marrow biopsy confirmed a diagnosis of acute myeloid leukaemia with inv(3)(q21.3q26.2) with additional monosomy 7. Central diabetes insipidus (DI) was diagnosed following a water deprivation test. Pituitary magnetic resonance imaging show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Acute and chronic leukemia may also present as a sellar mass lesion, thickened pituitary stalk or infiltration of a pituitary adenoma by leukemic cells [34][35][36][37][38][39][40]. An autopsy study of more than 1,200 patients who died due to acute or chronic leukemia showed that up to 20% of patients had infiltration of the pituitary gland [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute and chronic leukemia may also present as a sellar mass lesion, thickened pituitary stalk or infiltration of a pituitary adenoma by leukemic cells [34][35][36][37][38][39][40]. An autopsy study of more than 1,200 patients who died due to acute or chronic leukemia showed that up to 20% of patients had infiltration of the pituitary gland [41].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, one patient had AML and presented with diabetes insipidus, while another patient was in the leukemic phase of non-Hodgkin B-cell lymphoma. In the literature, there are 84 cases of AML with diabetes insipidus, associated with worse outcomes [38,[42][43][44]. The underlying mechanism of diabetes insipidus in these 84 patients is still unclear since some patients may present with normal sellar MRI finding.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the question whether baseline glycated haemoglobin (HbA1c) dictates cardiovascular response to SGLT2 inhibitors, this does not appear to be the case from secondary analyses of cardiovascular and renal outcome trials. 1,2 Furthermore, in the Dapagliflozin And Prevention of Adverse outcomes in Heart Failure (DAPA-HF) trial, patients with symptomatic heart failure with reduced ejection failure randomised to dapagliflozin had a significantly lower risk of worsening heart failure or cardiovascular death compared to placebo, irrespective of the presence of diabetes (55% of patients did not have diabetes). 3 In relation to whether the cardiovascular benefits of SGLT2 inhibitors are dependent on glycaemic improvement, data from the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients-Removing Excess Glucose (EMPA-REG OUT-COME) trial demonstrates that cardiovascular death or hospitalisation for heart failure was similarly reduced in those subjects who did and did not experience a reduction in HbA1c in the first 3 months of treatment.…”
Section: General Correspondencementioning
confidence: 99%
“…3 In relation to whether the cardiovascular benefits of SGLT2 inhibitors are dependent on glycaemic improvement, data from the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients-Removing Excess Glucose (EMPA-REG OUT-COME) trial demonstrates that cardiovascular death or hospitalisation for heart failure was similarly reduced in those subjects who did and did not experience a reduction in HbA1c in the first 3 months of treatment. 1 In the Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CRE-DENCE) trial, there was a significant reduction in endstage kidney disease, a doubling of the serum creatinine level, or death from renal or cardiovascular causesin patients with type 2 diabetes and albuminuric chronic kidney disease (CKD) randomised to canagliflozin, despite an overall mean difference in HbA1c between the canagliflozin and placebo groups of only 0.25%. 4 Additionally, data from the three cardiovascular outcome trials (EMPA-REG OUTCOME, Canagliflozin Cardiovascular Assessment Study (CANVAS) and Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction 58 (DECLARE-TIMI 58)) demonstrates preserved cardiovascular benefits in people with CKD, 5 despite attenuated glycaemic effects in this population.…”
Section: General Correspondencementioning
confidence: 99%
“…When it occurs in patients with acute leukemia; it is often a poor prognostic indicator [ 2 ]. The gene for ADH is located at the cytogenetic location 20p13; however, most reports of patients with acute myeloid leukemia (AML) and diabetes insipidus (DI) describe cytogenetic aberrations of chromosomes 3 and 7 such as inv (3) (q21.3q26.2) and monosomy 7 [ 2 , 3 ]. Several mechanisms have been proposed to result in pituitary damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%